A fuzzy-genetic control system in the ABS for the control of semi-active vehicle suspensions. (November 2016) - Fargione, Giovanna; Tringali, Domenico; Risitano, Giacomo
Highlights: The aim of this paper is to create a new ABS control system of a Soft-Computing type, on the grounds of the excellent results obtained in the field of automobiles in former studies. A new control strategy of the physical nature of the hydraulic and electronic components based on a fuzzy-type algorithm optimised with genetic algorithms. The first target performance aimed is reduction in braking distance. The second target performance aimed is improved directional control of the vehicle. Abstract: The aim of this paper is to create a new ABS (Antilock Braking System) control system of a Soft-Computing type, on the grounds of the excellent results obtained in the field of automobiles in former studies [1]. Such a system should make it possible to enhance performance in all conditions. The novelty lies in the fact that the system improves not only the physical nature of the hydraulic and electronic components used [2, 3], but also the functioning of these, by means of a new control strategy based on a fuzzy-type algorithm optimised with genetic algorithms. In this way the performance of the system may be improved or alternatively the control logic may be simplified for the same degree of performance, offering satisfactory results in all possible conditions. The target performance aimed at may be summarised in two points: reduction in braking distance and improved directional control of the vehicle. The study was optimised on a monocorner model, subsequently to be extended to a complete vehicle model. Graphical abstract: Starting from the control logic most commonly used in standard vehicles an ABS strategy of a soft computing fuzzy type was developed. As a first step the system already on the market was analysed on the basis of the corresponding control logic found in literature, in order to characterise the thresholds of intervention.